QARAQALPAQ TILINDE SÍPAYÍLÍQTÍŃ QARATPA AǴZALAR ARQALÍ BILDIRILIWI - Matjanova, A.J. (SCIENCE and SOCIETY, 2024)
In this article, the meaning of politeness in the Karakalpak language is expressed with the help of exhortations. In order to communicate politely with the interlocutor, Karakalpaks use expressions of kinship, as well as nouns and adjectives denoting career, rank, and career. In official relations, the difference is felt in the occurrence of human names in the imperative function. In this case, the name of the person is used together with the name of the father. Differences in the use of exhortations are studied by comparing them with related languages